(untitled) (Damascus University Journal for the economic and Political sciences, 2021)
Our paper aims to clarify the impact of eco dimension on economic growth in Syria. For achieving this aim, we apply cointegration methodology (ARDL) method. We focus on five main indicators (Economic growth rate, Carbon dioxide, Alternative and nuclear energy, Electricity consumption, Agricultural land). The results clear that both electricity consumption and CO2 emissions have positive significant effect on economic growth in long run. Also, the results support for feedback hypothesis between economic growth and alternative-nuclear energy in both short-run and long-run. On the other side, Agricultural land effected negatively on the economic growth at 1 percent level of significance.